Analisis Upaya Sekuritisasi Mesir terhadap Grand Ethiopian Renaissance Dam (GERD) - Hafizh, Ibnu; Resen, Putu Titah Kawitri; Wiranata, I Made Anom (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2024)
In 2011, Ethiopia started the construction of the Grand Ethiopian Renaissance Dam (GERD), a large dam located in the upstream region of the Nile River. Egypt was concerned about the significant reduction in the water supply of the Nile caused by the GERD, which could lead to a water crisis. Egypt sees this matter as a security problem rather than just a water resource management issue. Egypt’s responses can be interpreted as an effort to securitize the matter. Using discourse analysis, securitization theory, and the concept of ideological square, this research aims to describe the securitization moves undertaken by Egypt towards the GERD. This study found that Egypt, through its statements, portrayed the GERD as a threat to national, regional, and international security. The securitization moves by Egypt functioned to provide deterrence, set the agenda of regional and international organizations, and legitimize future actions. Egypt also sought to build a positive image to gain support from the international society. This support was necessary for the success of its securitization moves and to exert greater pressure on Ethiopia. Perhaps the main objective of Egypt's securitization efforts was to maintain its hegemony over the water resources of the Nile.